Think Pair Share Technique to Promote Students' Reading Comprehension - Retno Dwigustini; Jenika Widiya (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2020)
The objective of the research is to promote students’ reading comprehension through Think Pair Share technique. The present research employed qualitative approach with Classroom Action Research (CAR) method. The participants involved were one class of seventh graders consisting of 22 students. The research was conducted in three cycles. Observation, test and interview were used to collect the data. The result revealed that 1) students’ score of reading comprehension  increases after the implementation of Think Pair Share technique (in cycle I, only 36% students passed the passing grade, in cycle II 73% of them passed the passing grade, and in cycle III, 100% students passed the passing grade; and 2) students’ motivation and learning excitement improve. The findings lead to a conclusion that this technique can promote students’ reading comprehension. It is then recommended for English teachers to keep using this technique as a solution to assist them in teaching reading comprehension and to motivate their students to be more active in learning.